Does foreign aid contribute to economic development? Evidence from micro data - Dunusinghe, P. (University of Colombo, 2017)
The relationship between foreign aid and economic development has been investigated extensively with the use of cross-country macro data, but the findings have remained inconclusive. The literature points to a number of problems with crosscountry studies, such as a lack of reliable and comparable data. Using micro-data, this study revisits the above relationship in a context of Sri Lanka depending markedly on foreign aid to pursue economic development. Specifically, it examines the impact of a foreign aid funded development project. This particular projecthas been in operation for over eight years in selected DS Divisions in the Kandy, Kegalle, Nuwara Eliya, and Monaragala Districts, and has assisted beneficiaries through a number of interventions such as tea and rubber outgrowing, entrepreneurship development, and social capital formation. In its analysis, this study triangulated evidence from different sources, namely a household survey, in-depth and key-informant discussions— covering both beneficiary and non-beneficiary households—and project monitoring and evaluation records. In particular, the study employed a quasi-experimental design based on the Propensity Score Matching approach. Results indicate that the average household per capita consumption and income, for both beneficiary and nonbeneficiary households, had significantly improved during the project period 2008- 2016. More importantly, per capita consumption and income of the project beneficiary households had increased much faster than that of the non-beneficiary households. In addition, beneficiary households had significantly improved their housing conditions, household assets, and access to basic facilities when compared with non-beneficiary households. Moreover, results indicate differential impacts across different districts and intervention types. Nevertheless, evidence suggests that the project had failed to achieve its intended development objectives to their maximum level. In other words, the project failed to achieve the rate of return expected at the beginning of the project, thereby highlighting the existence of suboptimal utilization of foreign funds.
Keywords: development project, foreign aid, impact evaluation, Sri Lanka